2009
DOI: 10.1016/j.aorn.2008.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Knowledge of Inadvertent Hypothermia

Abstract: Inadvertent hypothermia can have significant consequences in the perioperative setting. Knowing how to recognize and manage inadvertent hypothermia is an important aspect of perioperative nursing. A quantitative, descriptive study was conducted at an annual perioperative nursing conference to evaluate nurses' knowledge regarding the prevention of inadvertent perioperative hypothermia. Significant variations in responses regarding definitions of hypothermia and normothermia were noted. In addition, nurses ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
1
11

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 15 publications
6
42
1
11
Order By: Relevance
“…Significantly, nurses involved with neonates need adequate knowledge about different procedures and their implementation to provide safe and necessary newborn care (Hegarty et al. ). According to Baqui et al.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly, nurses involved with neonates need adequate knowledge about different procedures and their implementation to provide safe and necessary newborn care (Hegarty et al. ). According to Baqui et al.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] On average, patients undergoing surgery will have a core temperature heat loss of between 1 C and 3 C. 4 Three principle factors are said to contribute to this occurrence:…”
mentioning
confidence: 99%
“…6,7 Staff development sessions about the risk factors, contributing factors, and best approaches to avoiding unintentional hypothermia (such as preoperative warming) remain necessary. Two studies found a gap in nurses' knowledge about unintentional hypothermia.…”
Section: Knowledge Gapmentioning
confidence: 99%